2001
DOI: 10.1016/s0006-3223(00)01111-2
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and amyloid formation

Abstract: The major protein constituents of amyloid deposits in Alzheimer's disease (AD) are the 40-residue ␤-amyloid (A␤)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 53 publications
8
49
1
Order By: Relevance
“…Gratifyingly, the diffusion coefficients resulting from the DECRA analysis are in agreement with those obtained from DOSY analysis of the data. Further corroborative evidence of covalent modification can been seen by analyzing nicotine-A␤ incubations as nicotine can only inhibit aggregation via a noncovalent mechanism (39,40). In this data set, two populations of nicotine molecules cannot be observed (data not shown).…”
Section: Covalent Modification Of A␤ By Nornicotine and Inhibition Ofsupporting
confidence: 55%
See 1 more Smart Citation
“…Gratifyingly, the diffusion coefficients resulting from the DECRA analysis are in agreement with those obtained from DOSY analysis of the data. Further corroborative evidence of covalent modification can been seen by analyzing nicotine-A␤ incubations as nicotine can only inhibit aggregation via a noncovalent mechanism (39,40). In this data set, two populations of nicotine molecules cannot be observed (data not shown).…”
Section: Covalent Modification Of A␤ By Nornicotine and Inhibition Ofsupporting
confidence: 55%
“…The beneficial effects of nicotine have been attributed to a number of factors including an up-regulation of nicotine receptors that are deficient in the brain, or possibly a protection from the A␤-induced neurotoxicity (38). Others have postulated that nicotine also serves another role by inhibiting ␤-amyloidosis through noncovalent binding to either the ␣-helical structure of A␤ (39) or a small, soluble ␤-sheet aggregate (40).…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have shown that nicotine may actually improve short‐term cognitive performance7, 30 and inhibit amyloid formation 31, 32. On the other hand, various other studies have shown that smoking is a risk factor for Alzheimer's disease, namely due to reactive oxygen species produced by smoking 33, 34, 35, 36, 37.…”
Section: Discussionmentioning
confidence: 99%
“…Tomiyama et al (1996) suggested that Rif binds to Aß by hydrophobic interactions between its lipophilic ansa chain and the hydrophobic region of Aß, thus blocking associations between Aß molecules leading to fAß formation. The anti-amyloidogenic and fibril-destabilizing activity of tetracycline (Tc), small-molecule anionic sulphonates or sulphates, melatonin, ß-sheet breaker peptides (iAß5) and nicotine may also be related to the propensity to bind to the specific sites of Aß (Kisilevsky et al 1995;Soto et al 1996;Pappolla et al 1998;Forloni et al 2001;Zeng et al 2001). Thus, it may be reasonable to consider that NSAIDs could exhibit their anti-amyloidogenic and fibril-destabilizing effects by directly binding to Aßs and/or fAßs.…”
Section: Discussionmentioning
confidence: 99%